2002
DOI: 10.1177/108835760201700101
|View full text |Cite
|
Sign up to set email alerts
|

Employers' Attitudes Toward Persons with Disabilities in the Workforce

Abstract: A review of literature on employers' attitudes toward workers with disabilities was completed. Factors that may affect employers' attitudes toward persons with disabilities in the workforce are provided, as well as a description of the methodologies used in the investigations. Although several key themes emerge, decades of employer attitudinal research has generally produced inconsistent findings due to variations in research design.ajor legislative and philosophical forces during the past 30 years have attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
184
1
16

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(212 citation statements)
references
References 12 publications
(31 reference statements)
11
184
1
16
Order By: Relevance
“…Предрасуде према особама са ометеношћу имају ко-рене у недостатку знања и одржавању погрешних, често негативних стереотипа (Unger, 2002;Wells, 2001). Многи послодавци и даље верују да су радници са ометеношћу непоуздани, непродуктивни, конфликтни, да угрожавају безбед-ност сарадника, да чешће изостају с посла од колега опште популације, да адап-тација радног места за њих изискује знатна финансијска улагања и да утичу на културу и климу предузећа.…”
Section: ставови према запошљавању особа са ометеношћуunclassified
“…Предрасуде према особама са ометеношћу имају ко-рене у недостатку знања и одржавању погрешних, често негативних стереотипа (Unger, 2002;Wells, 2001). Многи послодавци и даље верују да су радници са ометеношћу непоуздани, непродуктивни, конфликтни, да угрожавају безбед-ност сарадника, да чешће изостају с посла од колега опште популације, да адап-тација радног места за њих изискује знатна финансијска улагања и да утичу на културу и климу предузећа.…”
Section: ставови према запошљавању особа са ометеношћуunclassified
“…Concerns about hiring persons with a mental illness often centres on functional performance and emotional stability in the workplace (Kosyluk, Corrigan, Todd & Bodenhausen, 2010;Landis, 2014;Diska & Rogers, 1996). Meanwhile, employers with past experiences of hiring people with a mental illness or severe disability have been found to have more positive views about hiring such persons in the future (Kosyluk et al 2014;Diska & Rogers, 1996;Levy, Jessop, Rimmerman & Levy, 1991).…”
Section: Employer Concernsmentioning
confidence: 99%
“…In their studies of employer hiring decisions concerning people with severe psychiatric disorders, Kosyluk et al, (2014) also noted that not only were past experiences associated with the hiring of persons with mental illness positive, they were also inversely related to previously held views of stigma, although employers demonstrated a much higher preference for hiring persons with physical rather than mental disability. Similarly, Unger (2002) points out that employer views in relation to hiring persons with a mental disorder indicated that they thought this would be problematic, and grouped such concerns with employees around issues related to expected displays of emotional disturbance. Similarly, Hand, Tryssenaar, William, and Gill (2006) found that one of the biggest concerns small business employers have is that prospective employees with a mental illness may have poor social skills and may be overly emotional in the workplace.…”
Section: Employer Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…그동안 장애인 고용을 결정하는 데 영향을 미치 는 요인 중 장애인 고용에 관한 인식을 조사한 국 외 연구를 보면, 근로자의 장애유형 [12], 장애인과 이전의 경험 [12], 사업체 유형 [12], 장애인고용 만족 도 [12], 지원제도 및 법적 규제 [13] …”
unclassified